Economic and environmental determinants of the health condition of the Filipinos - Orejana, Anne Jalandoni (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 2010)
Economic development has always been the target of economic policies because higher output brings about improvement in welfare in terms of the country's ability to provide the necessary social services. But when development efforts are aggressively pursued to the extent of causing environmental degradation and natural resource depletion, this would also cause adverse effects to human welfare in terms of health. With this two opposing forces, this research endeavors to establish the groundwork that would identify the effect of economic development and environmental factors on the health conditions of Filipinos. The growing awareness of looking after the health welfare and good quality of life for the Filipinos, and the realization that environmental protection is a requisite for good health, the findings of this study can provide insights to policymakers and a groundwork for the review and formulation of development policies and programs to ensure sustainable development by putting environmental issues at the heart of economic policies. Using data for the Philippines from 1980 to 2004, health indicators like crude death rate, infant mortality rate, maternal mortality rate and life-expectancy at birth were analyzed with economic indicators such as GNP per capita, level of industrialization and Government health expenditure per capita; and environmental indicators such as Carbon-Dioxide emission, Particulate Matter on air and Bio-Oxygen Demand. Over the 25-year period, an improvement in all of the four health indicators is observed. Among the factors identified, Carbon-Dioxide Emission strongly and significantly explains the variation in the three (3) health indicators used namely: Crude Death Rate, Infant Mortality Rate and Life Expectancy at birth. Crude Death Rate in particular can be explained by both economic and environmental indicators but none of the factors could explain the overtime variation in maternal mortality rate of the Philippines.